3D Printing of Tunable Energy Storage Devices with Both High Areal and Volumetric Energy Densities. Issue 8 (27th December 2018) - Gao, Tingting; Zhou, Zhan; Yu, Jianyong; Zhao, Jing; Wang, Guiling; Cao, Dianxue; Ding, Bin; Li, Yiju
Abstract: Developing advanced supercapacitors with both high areal and volumetric energy densities remains challenging. In this work, self‐supported, compact carbon composite electrodes are designed with tunable thickness using 3D printing technology for high‐energy‐density supercapacitors. The 3D carbon composite electrodes are composed of the closely stacked and aligned active carbon/carbon nanotube/reduced graphene oxide (AC/CNT/rGO) composite filaments. The AC microparticles are uniformly embedded in the wrinkled CNT/rGO conductive networks without using polymer binders, which contributes to the formation of abundant open and hierarchical pores. The 3D‐printed ultrathick AC/CNT/rGO composite electrode (ten layers) features high areal and volumetric mass loadings of 56.9 mg cm −2 and 256.3 mg cm −3, respectively. The symmetric cell assembled with the 3D‐printed thin GO separator and ultrathick AC/CNT/rGO electrodes can possess both high areal and volumetric capacitances of 4.56 F cm −2 and 10.28 F cm −3, respectively. Correspondingly, the assembled ultrathick and compact symmetric cell achieves high areal and volumetric energy densities of 0.63 mWh cm −2 and 1.43 mWh cm −3, respectively. The all‐component extrusion‐based 3D printing offers a promising strategy for the fabrication of multiscale and multidimensional structures of various high‐energy‐density electrochemical energy storage devices. Abstract : The all‐graphene‐oxide (GO)‐based symmetric supercapacitor is assembled with a thin GO separator and compact active carbon/carbon nanotube/reduced graphene oxide composite electrodes with tunable thickness, which are fabricated using the advanced extrusion‐based 3D printing technology. The 3D‐printed ultrathick and compact symmetric supercapacitor with a high mass loading can achieve both high areal and volumetric energy densities.